A robust and stable nano‐biocatalyst by co‐immobilization of chloroperoxidase and horseradish peroxidase for the decolorization of azo dyes. Issue 2 (13th September 2017) - Jin, Xinyu; Li, Saisai; Long, Nengbing; Zhang, Ruifeng
Abstract: BACKGROUND: Immobilization of more than one peroxidase on the same support is an ideal technology for application because such a multi‐enzyme catalytic system may show high activity over a very wide optimal range of pH, temperature and H2 O2 concentration. In this work, chloroperoxidase (CPO) and horseradish peroxidase (HRP) were co‐immobilized on ZnO nanowires/macroporous SiO2 composite support through an in situ cross‐linking method. An anionic bi‐epoxy cross‐linker was used by adsorption on the surface of ZnO nanowires before cross‐linking. RESULTS: The cross‐linking was carried out under suitable conditions: pH 6.5, reaction temperature 15°C and reaction time 15 h. Using a 1/1 mixture of CPO and HRP resulted in a co‐immobilized enzyme with loading 79.6 mgCPO g ‐1 support and 52.8 mgHRP g ‐1 support, and total specific activity up to 15.7 U per mgsupport . The co‐immobilized enzyme also showed good stability after 60 days of storage, and excellent reusability over 20 repeat uses. CONCLUSIONS: For the decolorization of azo dyes the co‐immobilized CPO (60%)/HRP (40%) exhibited high catalytic activity over very wide ranges of pH, temperature and H2 O2 concentration. Using this robust biocatalyst, complete decolorizations of azo dyes have been realized within 3 h of reaction. © 2017 Society of Chemical Industry